Overexpression of SSBXoc, a Single-Stranded DNA-Binding Protein From Xanthomonas oryzae pv. oryzicola, Enhances Plant Growth and Disease and Salt Stress Tolerance in Transgenic Nicotiana benthamiana - Cao, Yanyan; Yang, Mingtao; Ma, Wenxiu; Sun, Yujing; Chen, Gongyou (Frontiers in Plant Science, 2018)
We previously reported that SSBXoc, a highly conserved single-stranded DNA-binding protein from Xanthomonas spp., was secreted through the type III secretion system (T3SS) and functioned as a harpin-like protein to elicit the hypersensitive response (HR) in the non-host plant, tobacco. In this study, we cloned SsbXoc gene from X. oryzae pv. oryzicola (Xoc), the causal agent of bacterial leaf streak in rice, and transferred it into Nicotiana benthamiana via Agrobacterium-mediated transformation. The expression of SsbXoc in transgenic N. benthamiana enhanced growth of both seedling and adult plants. When inoculated with the harpin Hpa1 or the pathogen Pseudomonas syringae pv. tomato DC3000 (Pst DC3000), the accumulation of reactive oxygen species (ROS) was increased more in SsbXoc transgenic lines than that in wild-type (WT) plants. The expression of pathogenesis-related protein genes (PR1a and SGT1), HR marker genes (HIN1 and HSR203J) and the mitogen-activated protein kinase pathway gene, MPK3, was significantly higher in transgenic lines than in WT after inoculation with Pst DC3000. In addition, SsbXoc transgenic lines showed the enhanced resistance to the pathogenic bacteria P. s. tabaci and the improved tolerance to salt stress, accompanied by the elevated transcription levels of the defense- and stress-related genes. Taken together, these results indicate that overexpression of the SsbXoc gene in N. benthamiana significantly enhanced plant growth and increased tolerance to disease and salt stress via modulating the expression of the related genes, thus providing an alternative approach for development of plants with improved tolerance against biotic and abiotic stresses.